Bacterial RadA is a DnaB-type helicase interacting with RecA to promote bidirectional D-loop extension - Léa Marie (Nature Portfolio, 2017)
Bacterial homologous recombination involves the actions of RadA and RecA to promote single-stranded DNA integration. Here the authors report the structure of RadA fromStreptococcus pneumoniaeand demonstrate that it acts as a hexameric DnaB-type helicase.